Assessing the integration of gender equality and social inclusion in landscape management related policies in Ghana: a review - Oyawole, F. P.; Osei-Amponsah, Charity; Atampugre, Gerald; Tilahun, Seifu A.; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2024)
Rising demands for natural resources threaten landscape sustainability. This underscores the need for sustainable landscape management, which necessitates inclusivity, equitable decision-making, and collaborative action. This documentary review examines Gender Equality and Social Inclusion (GESI) integration in Social-Ecological Landscape (SEL) management related policies at the national, sectoral and district levels in Ghana. The results indicate that Ghana demonstrates commitment to GESI through national policies like the National Gender, Youth and Social Protection Policies, which provide a framework for GESI mainstreaming across all sectors and levels of governance. However, while some policies like the Medium-Term National Development Policy Framework and agricultural policy fully integrate GESI, notable gaps exist in others, like the water, forestry and mining policies, which lack specific measures to address inclusivity in resource access and transformation of discriminatory institutional structures. The study recommends GESI gap analyses to identify inequalities and marginalized groups, policy revision and development of context-specific GESI responsive strategies, particularly at the sectoral level. Bridging these GESI gaps will not only enhance the wellbeing of marginalized groups, but also foster more sustainable management of Ghana's landscapes.